Thrombotic Complications in Gliomas - Czap, Alexandra L.; Becker, Ashley; Wen, Patrick Y. (Seminars in Thrombosis and Hemostasis, 2019)
Arterial and venous thromboses are common in glioma patients, both in the perioperative period and throughout the course of the disease. High-grade glioma patients harbor underlying hypercoagulability, which predisposes these high-risk patients with prolonged immobility and neurologic deficits to thrombotic events. Despite the high incidence and recurrent nature of these complications, there is no standardized approach to the management of glioma patients, and many challenges remain. Historically, the perceived risk of intracranial and intratumoral hemorrhage limited the use of anticoagulation, favoring nonpharmacological prophylaxis and treatment. Multiple studies have demonstrated the safety and efficacy of anticoagulation when indicated, with low molecular weight heparin as the preferred short- or long-term treatment. This review will discuss the epidemiology, risk factors, and therapeutic management of both venous and arterial thrombotic complications in glioma.
Keywords: glioma; thromboembolism; deep venous thrombosis; pulmonary embolism; ischemic stroke